2013
DOI: 10.1063/1.4790567
|View full text |Cite
|
Sign up to set email alerts
|

Translational diffusion of probe molecules under high pressure: A study by fluorescence recovery after photobleaching technique

Abstract: International audienceWe present fluorescence recovery measurements after photobleaching performed under high pressure in liquids that fill square-section fused silica micro-capillaries. These micro-capillaries withstand pressure up to 2500 bar for a wall thickness of about 140 μm and fit easily on the microscope stage. This technique allows the translational diffusion coefficient of fluorescent molecules in liquids to be measured as a function of pressure. When the liquid sample is far from its glass transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 42 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Along the isotherm at T = 30 °C their measurements show that the shear viscosity varies exponentially with pressure with an ∼2.5 orders of magnitude increase between atmospheric pressure and 0.4 GPa. Because of the lack of high-pressure viscosity measurements for PPG-1000M, we assume that the viscosities of PPG and PPO obey the same pressure dependence: where μ 0 ( P = 0.1 MPa) is the shear viscosity depending on the polymer and c = (6.2 ± 0.4) × 10 –3 MPa –1 is constant for both PPG and PPO. For PPG-1000 M the value of μ 0 ( T ) is taken from Baur et al Figure shows that up to ∼0.3 GPa the normalized diffusion coefficient D / D SE is centered around 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Along the isotherm at T = 30 °C their measurements show that the shear viscosity varies exponentially with pressure with an ∼2.5 orders of magnitude increase between atmospheric pressure and 0.4 GPa. Because of the lack of high-pressure viscosity measurements for PPG-1000M, we assume that the viscosities of PPG and PPO obey the same pressure dependence: where μ 0 ( P = 0.1 MPa) is the shear viscosity depending on the polymer and c = (6.2 ± 0.4) × 10 –3 MPa –1 is constant for both PPG and PPO. For PPG-1000 M the value of μ 0 ( T ) is taken from Baur et al Figure shows that up to ∼0.3 GPa the normalized diffusion coefficient D / D SE is centered around 1.…”
Section: Resultsmentioning
confidence: 99%
“…The recovered spot fluorescence intensity is the spatially integrated product of the intensity profile of the reading beam with the concentration distribution of unbleached molecules that diffuse into the bleached area. For 2-D diffusion many analytical expressions have been derived to fit the recovered time-dependent fluorescence intensity and deduce the diffusion coefficient of the fluorescent molecules. ,, In a previous article, we have shown that a single-exponential function can fit the data on a time scale as large as 10 times the diffusive time. Van Keuren and Schrof derived a simple analytical expression for the fluorescence recovery in a small region centered on the bleached spot.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations